Analysis Of The Effect Of Distribution Costs On Sales Volume At PT. Timur Jaya - Agung Soedibyo; Nuryadi (International Journal of Economics, Science, and Education, 2024)
This study aims to (1) determine the amount of sales volume at PT. Timur Jaya Sentosa from 2018 to 2020 , (2) determine the amount of distribution costs at PT. Timur Jaya Sentosa from 2018 to 2020. And (3) determine the effect of distribution costs on sales volume at PT. Timur Jaya Sentosa from 2018 to 2020. The results of this study indicate that the sales volume of PT. Timor Jaya Sentosa always increases every year, and the Distribution Costs incurred by PT. Timor Jaya Sentosa always increase every year. And based on the hypothesis testing, there is a positive and significant effect of distribution costs on the sales volume of PT. Timur Jaya Sentosa